Studies on the vignettes from chapter 17 of the Book of the dead : I : the image of mś.w Bdšt in ancient Egyptian mythology - Tarasenko, Nikolaĭ (Archaeopress Egyptology, 2016)
This work is a comprehensive study of the myth of the Egyptian deities mś.w Bdšt, 'Children of Weakness', and the scene depicting the cat, cutting off the head of the serpent under the branches of the išd-tree found on a number of 'Book of the Dead', chapter 17 vignettes